Nové nálezy tmavoretky bělavé Monacha cartusiana (O. F. Müller, 1774) ve Strakonicích a okolí - Vilém Hrdlička; Eva Legátová (Malacologica Bohemoslovaca, 2023)
The thermophilous land snail Monacha cartusiana has been spreading in Central Europe in recent years, presumably as a consequence of warming. In the years 2020–2022, several new localities of this snail were discovered in Strakonice, Horažďovice, and Putim (South Bohemian Region, Czechia). All of them are concentrated around roads or railways. Due to the nature of these biotopes, the fate of these populations is uncertain in the future.